145 Evidence gap map (EGM)s: a policy makers tool for navigating the evidence landscape. a case study of employment and health from the systems science in public health and health economics research (SIPHER) project. (10th September 2022) - Campbell, Fiona; Chambers, Duncan; Wong, Ruth; Llewellyn, Jennifer; Elsenbroich, Corinna
Abstract : Objectives: Policy decisions are often made in complex, interlinked systems. Providing evidence to support policy making decisions within this context presents methodological challenges. Policy makers have multiple information needs, looking at broader topics. In contrast, systematic reviews usually address a very specific question, examining a particular intervention or exposure. Policy makers timeframes are usually shorter than the time needed to undertake a systematic review and the outputs of evidence synthesis are often unwieldy to process and are quickly out of date. In addressing the broad topic of the relationship between employment and health, we undertook a mapping review and produced a mega-map as an interactive, visual web-based tool. The tool allows multiple questions to be addressed and a range of types of evidence synthesis quickly identified and provides links to the abstract and full text. Method: We used systematic approaches, searching seven bibliographic databases, to locate and include review level evidence that measured associations of employment and unemployment with physical, psychological and social health and wellbeing outcomes. We limited our search strategy to those reviews published since 2010 and only included published systematic reviews. In collaboration with our stakeholders, we constructed a framework of employment-related exposures (row headings) and health and social wellbeing outcomes (column headings). Filters, allow further exploration of the map. The features of employment we considered was comprehensive including; employment conditions, contractual arrangements, management styles, working patterns, specific working populations and transition periods such as returning to work. Included studies were coded using the prepared framework. Coding was undertaken by three reviews independently, using Eppi-Reviewer and Eppi-Mapper software. We are incorporating an ongoing evaluation of the EGM in order to determine how to improve the utility of the tool for policy decision making Results: Initial database searches identified 4, 087 potentially relevant studies, and following screening 239 systematic reviews were included in the map. The EGM provides an overview of the volume, diversity and the type of evidence syntheses that have explored the relationship between aspects of employment and health and social wellbeing. We created filters so that the types of systematic reviews could be readily identified, categorising those using a meta-analysis (n=43), meta-analyses and meta-regression (n=24), narrative (n=163) or qualitative methods of synthesis (n=9). The interactive table allows a visual picture of where a review exists and takes the user to an abstract of the review and DOI link. Gaps in the evidence base can be readily identified. Filters enable exploration of the evidence for specific populations. Notable gaps in the evidence were highlighted, e.g. the impact of unpredictable work and the effects of different types of employment on young people's health and wellbeing. Conclusions: The EGM provides a useful tool that addresses the complexity of the policy making environment, where multiple questions may be being asked and time frames in which decisions are made preclude waiting for the results of a full systematic review. As a visual interactive tool it allows users to locate readily the evidence needed to address specific questions for particular populations. The map also gives an indication of the trustworthiness of the review findings. The EGM also provides a link to the source evidence. Limitations of the tool include the fact that the reviews are coded but their findings are not synthesized. This case study is allowing up to explore the use of different visual evidence synthesis products in supporting decision making in complex policy settings.